Ahmad Kasravi and "Pick-Axe Politics": Neckties and Literature as Western Tools of Cultural Imperialism. Issue 1 (1st March 2016) - Ridgeon, Lloyd
Abstract: Cultural authenticity has occupied the minds of Iranian intellectuals from the nineteenth century onwards, and Ahmad Kasravi (d. 1946) was among the greatest supporters of an Iran whose independence included not just territorial integrity but the freedom to choose elements of its heritage that were compatible with a modern nation-state. Kasravi attempted to identify those elements of Iranian culture that he believed were based on reason, and rejected much of the heritage that did not conform to his rigorous standards. As an example of how he tried to purify twentieth-century Iran, this article investigates how he identified aspects of Western culture and assesses his response to the "pick-axe politics" of the imperialist powers.